Framework for mitigating the risk of waterborne diarrheal diseases in peri-urban areas of Lusaka district Zambia - Ncube, Esper Jacobeth (University of Pretoria, 2023)
Thesis (PhD (Public Health))--University of Pretoria, 2023.